Psycho shifters - Mas, Jasmine (Mas, Jasmine. Cruel shifterverse, 2025)
"Fight like a girl...or a shifter of lore. After growing up with nothing, I've finally found my path to freedom: I'm an alpha shifter, an elite soldier who transforms into a monster. All I have to do is survive training at a war camp. But I didn't count on my three 6'5 alpha roommates. Covered in tattoos, jeweled, and horned, these are like no men I've ever dealt with before. They don't think I belong. They don't think I'm strong enough for war. They don't think I'm an alpha. But can I survive them discovering the secrets of my past? In the battle for life and death, everyone is so much more than they seem. Jax, Ascher, and Cobra are going to be devastated when they discover my truth...just wait until they see my shifted form"--Back cover.